Accidental Wilderness : The Origins and Ecology of Toronto's Tommy Thompson Park - Kehm, Walter H., 1937- (Book collections on Project MUSE., 2020)
"Once referred to as Toronto's "accidental wilderness," Tommy Thompson Park is now recognized as a fortuitous urban miracle. Initially created as a landfill site on the city's rapidly developing waterfront, the park's physical and ecological footprint have grown dramatically. Forests, grasslands, and wildlife now thrive - all within a stone's throw of some of the most densely populated areas of North America's fourth-largest city. Accidental Wilderness is a rich and lyrical collection of essays curated by internationally recognized landscape architect and original designer of Tommy Thompson Park, Walter H. Kehm, complemented by a stunning collection of photographs by renowned landscape photographer Robert Burley. The book explores the city's port origins; the park's master plan principles and design; the native-plant succession process; the park's unique flora and fauna; public advocacy; and public recreation in the park and its effect on mental, physical, and spiritual health. In an era where the looming dangers associated with climate change affect our daily lives, Tommy Thompson Park offers a hopeful narrative about how nature can flourish in, and contribute to, the well-being of twenty-first-century cities."--